STEM Media in the Family Context: The Effect of STEM Career and Media Use on Preschoolers' Science and Math Skills - Kelly Jean Sheehan; Brianna Hightower; Alexis R. Lauricella; Ellen Wartella (Lectito Journals, 2018)
Children's learning of science, technology, engineering, and mathematics (STEM) is important for their achievement in related fields. Before formal schooling, families can expose children to STEM by sharing knowledge and influencing children's use of learning tools, including media. We investigated whether parent attitudes towards STEM media and having a family member with a STEM career is related to children's science and math media use, and whether these factors predict children's science and math skills. We surveyed 296 American parents of children 3- to 5.5-years old on their attitudes toward STEM and their children's use of STEM television, computer games, and apps. Regression analyses showed that positive attitudes toward science and math media positively predicted children's science and math media use. Having a STEM-career family member was a negative predictor. Children's science and math media use was negatively related to their reported science and math skills. However, there was an interaction: children from non-STEM career families who consumed the most science and math media reportedly had worse science and math skills. Our findings have implications for how families can support science and math learning. These results can direct research on the role of media in early STEM education.